Comparative Study of Antimalarial Effect of Sambiloto (Andrographis paniculata) Extract, Chloroquine and Artemisinin and Their Combination Against Plasmodium falciparum In-vitro - Umar Zein; Loeki E Fitri; Awaluddin Saragih (Acta Medica Indonesiana, 2013)
Aim: to compare the anti-malarial effect among sambiloto extract, chloroquine and artemisinin-only as well as those of their combination. Methods: the study was conducted in Central Biomedical Laboratory, Faculty of Medicine, Brawijaya University, Malang, Indonesia from January to February 2006. Malaria culture used Plasmodium falciparum of Papua strain (2300) that was obtained from Namru-2 Jakarta. Five drugs applied in this test; those were chloroquine, artemisinin, the extract of sambiloto, the combination of sambiloto and chloroquine, and the combination of sambiloto and artemisinin. Parasite density was determined by counting the number of Plasmodium falciparum infected erythrocyte in 5,000 erythrocytes of the culture. Single drug (Chloroquine-only or artemisinin only) and either combination with sambiloto at dose 0.5 ug/ml had killing-effect against the parasite, measured by the appearance of “crisis form” on the infected erythrocytes. This killing-effect was dose dependent, and reached its optimum effect of 200 ug/ml. Results: treatment of single sambiloto extract with dose 0.5 ug/ml increased the density of the parasite, however after every 1ug increasing dose of sambiloto extract, the killing effect also increased. The reduction of the parasite density was also seen by increasing the Sambiloto dose in the group of combination of sambiloto-chloroquine as well as the group of combination of sambiloto and artemisinin. Statistically, there was no difference in the anti-malaria efficacy among of five test drugs (p=1.00). The correlation between the reduction of the parasite with the increasing of dose in all groups is statistically significance (p=0.001). Conclusion: the extract of sambiloto in a single dose or in a combination evidently has the effect of anti-falciparum malaria.